The reality of the application of transformational leadership among educational supervisors; Descriptive and analytical study - Alobaidani, Khulood Ahmed Amur; bent Hashim, Noor hayati (Journal of Educational and Psychological Sciences, 2020)
This study aimed to reveal the practice of educational supervisors for transformational leadership supervision and its relationship to their practice of educational supervision. And the correlation between them. The study relied on the descriptive analytical method. The study population consists of all (121) supervisors of the first field of education for the academic year (2018/2019). The study sample included (85) supervisors selected by simple random sample method. The questionnaire was used and consisted of the transformational driving axis. The results of the study showed that the degree of exercise of educational supervisors to the dimensions of transformational leadership was moderate with a mean of the overall arithmetic (3,47) came first place dimension first: the ideal effect (3.73) and followed in the second place: individual considerations (3, 65) In the third place: intellectual stimulation (3.24) and in the last place: inspirational motivation (3.24), the average indicates that the educational supervisor does not apply transformational leadership during supervisory and school visits. The results of the study also showed a strong correlation Between the practice of transformative driving dimensions, and the dimensions of ANS Educational Supervision: The correlation coefficient reached (0.622), while the correlation coefficient square (R²), (0.387); an explanatory capacity (35.6%) of the degree of educational supervisors practice the elements of educational supervision, and this is an indication of the existence of interdependence between them but not applied in practices Educational Supervisor.
Keywords: transformational leadership; Transformational Leadership Supervision